2016
DOI: 10.1038/pcan.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Berbamine inhibited the growth of prostate cancer cells in vivo and in vitro via triggering intrinsic pathway of apoptosis

Abstract: BBM exhibited strong anti-PCa activities in vitro and in vivo relying on activating caspase-3 via intrinsic pathway of apoptosis, holding a great promise to develop new strategies for PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…This work is the first report focused on exploring the antiproliferative, cytotoxic and apoptosis-inducing effects of bersavine. In previous studies, the structurally related alkaloid berbamine was clearly confirmed as a promising anticancer drug candidate, which was supported by experimental evidence of strong antiproliferative, cytotoxic and proapoptotic activity [6][7][8]12]. Moreover, berbamine is well-known in Chinese medicine and it has been used as a treatment option for decades [11].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This work is the first report focused on exploring the antiproliferative, cytotoxic and apoptosis-inducing effects of bersavine. In previous studies, the structurally related alkaloid berbamine was clearly confirmed as a promising anticancer drug candidate, which was supported by experimental evidence of strong antiproliferative, cytotoxic and proapoptotic activity [6][7][8]12]. Moreover, berbamine is well-known in Chinese medicine and it has been used as a treatment option for decades [11].…”
Section: Discussionmentioning
confidence: 78%
“…Berbamine also exerts anti-inflammatory effects by inhibiting nuclear factor-kappaB (NF-κB) and mitogen-activated protein kinase (MAPK) signalling pathways [7]. Its ability to inhibit proliferation in cancer cells was described repetitively in many experimental studies [8][9][10][11][12][13]. Zhang and coworkers observed the apoptosis-inducing effect of berbamine in colorectal cancer cells by activating p53-dependent apoptotic signalling pathways [14].…”
Section: Introductionmentioning
confidence: 99%
“…Du [24] found that BBM induced cell apoptosis and inhibited the cell proliferation through the PI3K/Akt pathway in lymphoma, the expressions of PI3K and p-Akt/Akt were down-regulated. Zhao [8] proved that BBM inhibited the activity of prostate cancer cells and could destroy the mitochondria of cells. All these researches indicated that the potential of BBM for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to possess the effects of anti-oxidation, immunoregulation, and anti-arrhythmia in recent studies [4][5][6][7]. BBM was also revealed to have potential function of antitumor [8][9][10]. However, there were few studies on the anti-tumor effect of BBM in lung cancer,and the in vitro studies just evaluated the cell activity and migration, and the mechanism involved was just Bcl-2/Bax.…”
Section: Introductionmentioning
confidence: 99%
“…5. Berbamine inhibited the growth of prostate cancer cells in vivo and in vitro via triggering intrinsic pathway of apoptosis [5]. Researchers discovered that Berbamine could inhibit prostate cancer progression via activating intrinsic apoptosis pathway, which offered an opportunity to develop new managing strategy for prostate cancer.…”
mentioning
confidence: 99%